Night in the haunted tower - West, Tracey (New York : Scholastic, 1999)
In order to defeat the Psychic Pokemon of Gym leader Sabrina and earn a Marsh badge, Ash and Pikachu must find and tame the Ghost Pokemon of Pokemon Tower.
Keywords: Ghosts -- Juvenile fiction; Fantasy fiction